Clinical-epidemiological characteristics of the pediatric patient with SARS-CoV-2 and dengue virus infection Servicio Desconcentrado Hospital Universitario pediátrico Dr. Agustín Zubillaga (Boletin Médico de Postgrado, 2025)
The World Health Organization warned that the simultaneous transmission of Dengue virus and SARS-CoV-2 in some regions could cause cases of confection and aggravation due to the overlapping of symptoms and the extra difficulty in management. The aim of this work was to determine the clinical-epidemiological characteristics of a group of pediatric patients with SARS-CoV-2 and Dengue virus infection who attended the Servicio Desconcentrado Hospital Universitario Pediatrico Dr. Agustín Zubillaga from July 2020 to 2023. In both viral infections, the highest percentage of infected patients was between the ages of 7 and 11 years, predominantly male. The most frequent symptom was fever, followed by bleeding and abdominal pain, and the predominant signs were skin rash and edema. All patients recovered and were discharged. In conclusion, a timely and early diagnosis of both infections allows an adequate management with a satisfactory evolution.